Homogenization of Bricket Dough: A Study on Horizontal Helical Ribbon Mixer - Ma'a, Mustaza; Adli, Muhammad Amirul; Novison, Roni; Wijianto, Agus; Nugraha, Nurcahya (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
The design of this briquette dough mixer machine is designed to mix briquette dough with a horizontal stirrer, the mixing knife used is a helix with two blades with different directions and sizes. This mixing machine uses a 1 HP AC motor with a motor speed of 1,400 Rpm, the engine also uses a 1:20 ratio gearbox, the rotation is obtained at 70 Rpm then reduced again to 50 Rpm using the pulley ratio so that the rotational speed achieved is 50 Rpm. The capacity of the mixing tube made is 10 kg in one mixing process, to be able to reach a capacity of 10 Kg requires matching the composition of the dough which consists of 5.75 Kg of charcoal, 0.287 Kg starch and 4.025 Kg water. In the process of mixing the dough, the starch is first dissolved in hot water, then slowly poured into the drum which has been filled with charcoal powder. Data collection was carried out by comparing 3 time variations, namely 10, 20 and 30 minutes. After mixing, the dough from each time variation was divided into 4 samples weighing 2.5 kg each and placed in different places. We can compare each time variation in terms of shape, texture and color so that we can analyze it. It was found from field experiments that to produce quality briquette dough, the mixing time was 30 minutes with an average power consumption of 2.49 KwH.